2021
DOI: 10.7759/cureus.14136
|View full text |Cite
|
Sign up to set email alerts
|

Clostridial Mycotic Aneurysm Leading to Emphysematous Aortitis

Abstract: Mycotic aneurysms account for less than 5% of all aneurysms of the aorta, with most cases linked to infection with either Staphylococcus or Salmonella species. Emphysematous aortitis is a rare consequence of mycotic aneurysms and is associated with high morbidity and mortality. It typically occurs from infection superimposed on already damaged endothelium, which is commonly seen in conditions such as atherosclerosis. This report discusses the presentation and relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Four of these patients had polymicrobial infections (aerobic and anaerobic bacteria including Streptococcus anginosus group SAG) and all of them showed gas bubbles on chest TC. Ng et al [ 60 ] reported the case of a 66-year-old man with Emphysematous aortitis from Clostridial infection of the thoracic aorta with presence of gas bubbles along the aortic wall. These findings were visible in the CT scan of the chest.…”
Section: Resultsmentioning
confidence: 99%
“…Four of these patients had polymicrobial infections (aerobic and anaerobic bacteria including Streptococcus anginosus group SAG) and all of them showed gas bubbles on chest TC. Ng et al [ 60 ] reported the case of a 66-year-old man with Emphysematous aortitis from Clostridial infection of the thoracic aorta with presence of gas bubbles along the aortic wall. These findings were visible in the CT scan of the chest.…”
Section: Resultsmentioning
confidence: 99%